2004
DOI: 10.1002/gcc.20046
|View full text |Cite
|
Sign up to set email alerts
|

DLEU2 encodes an antisense RNA for the putative bicistronic RFP2/LEU5 gene in humans and mouse

Abstract: Our group previously identified two novel genes, RFP2/LEU5 and DLEU2, within a 13q14.3 genomic region of loss seen in various malignancies. However, no specific inactivating mutations were found in these or other genes in the vicinity of the deletion, suggesting that a nonclassical tumor-suppressor mechanism may be involved. Here, we present data showing that the DLEU2 gene encodes a putative noncoding antisense RNA, with one exon directly overlapping the first exon of the RFP2/LEU5 gene in the opposite orient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 23 publications
1
34
0
Order By: Relevance
“…In allelic exclusion, one allele is silenced to ensure that the complex process of Ig gene recombination takes place only once. In 13q14.3, others and we observed excessive splicing of all large ncRNA genes (3,10,11). Because only genes from one of the chromosomes are expressed in 13q14.3, it is tempting to speculate that transcriptional and posttranscriptional complexity of the critical region requires silencing of the second chromosome similar to the Ig locus.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…In allelic exclusion, one allele is silenced to ensure that the complex process of Ig gene recombination takes place only once. In 13q14.3, others and we observed excessive splicing of all large ncRNA genes (3,10,11). Because only genes from one of the chromosomes are expressed in 13q14.3, it is tempting to speculate that transcriptional and posttranscriptional complexity of the critical region requires silencing of the second chromosome similar to the Ig locus.…”
Section: Discussionmentioning
confidence: 77%
“…To elucidate the role of DNA methylation of CpG island E associated with the ncRNA genes in 13q14.3, we wanted to test whether methylation of DNA or acetylation of histones are involved in the silencing effects at 13q14. 3. It has been shown that treatment with inhibitors of DNA methyltransferases [e.g., 5-aza-2Ј-deoxycytidine (5-aza-CdR)] or histone deacetylases [e.g., trichostatin A (TSA)] leads to euchromatinization in cell culture (27).…”
Section: Inhibitors Of Dna Methyltransferases and Histone Deacetylasementioning
confidence: 99%
See 2 more Smart Citations
“…Currently it is unclear whether the full length Dleu2 transcript is functionally important; however critical functions have been assigned to two genes encoded within Dleu2. In addition to miR15a/16-1, Dleu2 transcript also encodes an anti-sense for Dleu5 (also called Rfp2 of Trim13) (Corcoran et al, 2004). Dleu2 is transcribed from the reverse strand while Dleu5 is transcribed from the forward strand in Chr.13 in humans and Chr.14 in mice.…”
Section: Role Of 13q14 Locus In Cllmentioning
confidence: 99%